ANALISIS DESKIPTIF SISWA DENGAN DISLEKSIA DI SDN 2 SOMOROTO PONOROGO - Anugrah Putri, Ajheng Ervintari; Siswanto, Arif (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Dyslexia is a specific type of learning disability that has its origins in the functioning of the brain and cannot be explained by another diagnosis. It is characterized by reading difficulties that do not correspond to the child's age, intelligence or level of education. Children with learning disabilities generally experience concentration difficulties, memory problems and reading and writing difficulties. Dyslexic children face phonological difficulties: they have trouble recognizing letter sounds, associating letter names or symbols (graphemes) with the sounds they produce (phonetics), and dividing a word into its constituent sounds. This study therefore aims to determine the reading and writing profile of dyslexic students at SDN 2 Somoroto Ponorogo. This is qualitative research with an observational research design and a case study method of data collection. The sample used is 143 respondents and the sampling technique uses cluster sampling. The data analysis used was descriptive. The analysis identified 13 students with reading comprehension disorders, 2 students with dictation disorders and 1 student with dyslexia. The results indicate the need to pay particular attention to students with reading difficulties.